Evaluation of Warm‐Core Structure in Reanalysis and Satellite Data Sets Using HS3 Dropsonde Observations: A Case Study of Hurricane Edouard (2014). Issue 13 (2nd July 2018) - Gao, Si; Wang, Delong; Hong, Haixu; Wu, Naigeng; Li, Tim
Abstract: Using National Aeronautics and Space Administration Hurricane and Severe Storm Sentinel (HS3) dropsonde observations in the eye of Hurricane Edouard (2014), its warm‐core structure in reanalysis/analysis and satellite data sets are evaluated. All of the data sets generally underestimate the warm‐core strength of Edouard. Advanced Microwave Sounding Unit‐A shows the smallest error in the upper troposphere but the largest error in the lower troposphere. Its successor, Advanced Technology Microwave Sounder, significantly improves the representation of low‐level warming while maintaining its performance in the middle and upper troposphere. Two versions of the Global Forecast System analysis at different resolutions and Climate Forecast System Reanalysis version 2 show better performance than the other reanalyses. Modern Era Retrospective Analysis for Research and Application (MERRA)‐2, Japanese 55‐year Reanalysis, and European Centre for Medium‐Range Weather Forecasts Interim Reanalysis could represent the vertical warm‐core structure, but they markedly underestimate the warm‐core strength. MERRA and North American Regional Reanalysis (especially North American Regional Reanalysis) have the worst skills when reproducing warm cores. MERRA‐2 considerably outperforms its predecessor, MERRA. The warm‐core evolution of Edouard in six reanalysis/analysis data sets is diagnosed and compared. Different physical processes such as diabatic heating and vertical and horizontal advection may be responsible for warm‐core generation at different stages during its lifetime. The inaccurate representation of these physical processes in the reanalyses/analyses results in errors in the warm‐core strength and height. It is suggested that vortex relocation/bogusing, assimilation of tropical cyclone (TC) observation data, and model parameterizations are important to adequately represent warm cores in terms of strength and three‐dimensional structure. This study can shed some light on the selection of suitable data sets for estimating the real‐time warm‐core strength or for TC‐related climate studies. The need for better observations of TCs and model improvements is also highlighted. Key Points: ATMS better observes warm‐core structure in the lower troposphere compared to AMSU‐A The GFS analyses perform better in terms of representing warm‐core structure than the other reanalysis/analysis data sets The physical processes responsible for warm‐core evolution in the reanalyses/analyses are diagnosed and compared